Utilisation of transitional clusters exhibited within soccer game play to inform training design - Bortnik, L.; Burger, J.; Morgans, R.; Rhodes, D. (Scientific Journal of Sport and Performance, 2023)
The aims of this study were to investigate the effect of 15min blocks on physical metrics during transitions, analyse frequency, type, duration, and recovery period between clusters of transitional activities (CTA) in elite football. During ten official matches 23 elite footballers were tracked using GPS devices. Metrics per minute (m·min-1) as well as absolute variables: total distance (TD), high-speed running distance (HSRD > 19.8 km·h-1), sprint distance (SD > 25.2 km·h-1), relative high-speed running distance (VelB4), relative sprint distance (VelB5), acceleration distance (AccB3 Dist, distance with variations in running speed > 3 m·s-2), the number of high-intensity accelerations (HI Acc > 3 m·s-2) and decelerations (HI Dec > 3 m·s-2) were quantified. Significant effects of 15min blocks were found for TD (m) (p < .001; ES = .078), TD (m·min-1) (p = .047; ES = .036), HSRD (m) (p = .033; ES = .039), VelB4 (m) (p < .001; ES = .132), and HI Dec (n·min-1) (p = .002; ES = .059). Transitional activities recovery period was found to be 108.5 ± 26.2 s, CTA recovery period was 25.7 ± 3.6 s, while CTA peak duration reached 53.3 ± 18.2 s. This study indicates that physical metrics decrease in the last 15min blocks during transitions and high-pressure activities in games. In conclusion, repeated high intensity / high velocity activities frequently occur during contextualized peak intensity periods (transitions) in football, which should be reflected in modern training design.